APLICAÇÃO DE PIRIDOXINA SOBRE O CRESCIMENTO E PRODUTIVIDADE DA SOJA - Meira, Leonardo Borges Vasconcelos; TENÓRIO, João Pedro Barreto; VENDRUSCOLO, Eduardo Pradi; BORTOLHEIRO, Fernanda Pacheco de Almeida Prado; MARTINS, Murilo Battistuzzi; SERON, Cássio de Castro (ANAIS DO ENIC, 2025)
-